PENGARUH PEMBERIAN BERBAGAI PUPUK KANDANG DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN WORTEL (Daucus carota L) KULTIVAR KURODA EW - Rahman, Sigit Adithia; Dukat, Dukat; Budirokhman, Dodi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2025)
This study aims to determine the effect of various manures and spacing on the growth and yield of carrots (Daucus carota L). The research was conducted in Sanggarahiang Village, Darma District, Kuningan Regency, West Java. The location is located at an altitude of 1100-1200 meters above sea level (masl), the type of rain is type C (rather wet). The time of the research was carried out from July to November 2022. This study was arranged based on a randomized block design (RAK) with 2 treatment factors and 3 replications. The first factor was manure which consisted of three levels, namely chicken manure, goat manure and cow manure, while the second factor was plant spacing which consisted of three levels namely (25 cm x 20 cm), (30 cm x 20 cm) , and (35 cm x 20 cm). The results showed that the combination of chicken manure treatment and 30 cm x 20 cm spacing, then chicken manure and 25 cm x 20 spacing had a significant effect on the yield components, namely tuber length, tuber weight per sample and per plot. The results also showed that the combination of chicken manure treatment and a spacing of 25 cm x 20 cm gave a good average tuber weight per plot of 2,40 kg our equivalent 12,8 ton/ha.